Immune system of patients with tuberculosis uveitis during treatment (Ukrainian Journal of Ophthalmology, 2026)
Tuberculosis — a common infection which affected 19 to 43 % of the world population, due to the increasing incidence and emergence of severe. Purpose — determine the clinical course of tuberculosis uveitis depending on the immune system of patients.Material and method. The immune status of 134 patients with tuberculosis uveitis. Results. When tuberculosis eye leading role imbalance of immune regulatory subpopulations of T- lymphocytes as evidenced by the decrease in the total pool of blood T- lymphocytes by 41,3 %, T-helper — 22,1 %, B-lymphocytes — 13,8 % immune regulatory index — 2-fold increase against the background of T-suppres-sor cells by 69,3 % relative to control. The level oflg A and M increased — by 3.7 and 2.7 times in the decline of (53,8±1,42) % Ig G.Conclusions. A significant imbalance of immune regulatory subpopulations of T-lymphocytes and increased Ig A and M on background of Ig G indicates a clear breach of cellular and humeral immunity.
Keywords: tuberculosis uveitis; immune system